Pengolahan Sampah Terpadu Dengan Konsep Waste To Energy Di Smart City IKN - Rose, Ugahari; Kusumawati, Lili; Kurniyaningrum, Endah; Pontan, Darmawan; Widiarso, Tulus (Riviera Publishing, 2025)
In the context of the development of Indonesia’s new capital city in East Kalimantan, waste management presents increasingly complex challenges. Due to limited existing infrastructure, unintegrated waste management can lead to groundwater contamination, vegetation cover degradation, and threats to local biodiversity. This study aims to evaluate the implementation of an integrated waste treatment system combined with Waste to Energy (WtE) technology in the Capital City Area. Data were collected through direct observation and interviews with relevant stakeholders to measure the operational performance of the system. Field measurements included emissions analysis, energy production, and waste volume reduction. Based on a 15-day observation period in December 2024, thermal treatment produced only 2.97% residue. Assuming the operation of a single incinerator unit and limited waste supply, waste can be converted into electrical energy (Waste to Energy) with a power output of 195.169 watts. It can be concluded that by operating two incinerator units under the current conditions, the energy output could be doubled to 390.338 watts.